Ewing's Sarcoma of the Head and Neck: A Retrospective Analysis of 24 Cases. (1999) - Allam, Ayman; El-Husseiny, Gamal; Khafaga, Yasser; Kandil, Alaa; Gray, Alan; Ezzat, Adnan; Schultz, Henrik
Abstract : Introduction and purpose . Primary Ewing's sarcoma arising from the bones of the head and neck region is extremely rare representing only 1– 4% of all Ewing's sarcoma cases. Previous reports suggest a better prognosis for that particular anatomic site. The purpose of this study was to analyze the clinico-epidemiologic characteristics of that rare clinical presentation, as well as its patterns of failure and prognosis following treatment. Materials and methods. This study included a retrospective review of the medical records of patients with the diagnosis of Ewing's sarcoma of the head and neck region treated at King Faisal Specialist Hospital and Research Center between 1975 and 1996. Results . Out of a total number of 24 cases analyzed, there were 17 males and 7 females with a ratio of 2.4:1. The median age at diagnosis was 16.5 years. A painful swelling was the most common clinical presentation.The maxilla was the most common site of presentation (9/24 cases). There were 3/24 cases who presented with metastatic disease at diagnosis.The majority of patients (16/24 cases) had a tumor size >10 cm. Most patients were treated with systemic chemotherapy plus localized irradiation following an initial biopsy.With a mean follow up of 3.4 years, the 5-year actual overall survival (OS) for the whole group was 53%, while the 5-year actuarial disease-free survival (DFS) was 30%. These figures were higher than those repor ted from our institution for young patients (≤ 14 years treated for Ewing' s sarcoma in other anatomic locations (30% v 15%). The response to chemotherapy was the only prognostic factor that affected both the OS and DFS. Conclusion. The prognosis of Ewing's sarcoma of the head and neck region is slightly better than that of other anatomic sites.The response to systemic chemotherapy is one of the most important prognostic factors affecting both DFS and OS of Ewing's sarcoma of the head and neck. Multimodality therapy consisting of an initial biopsy, aggressive combination chemotherapy and localized radiotherapy is the treatment of choice for Ewing's sarcoma of the head and neck region and may result in long-term survival.